The taxonomic identity of some enigmatic darkling beetle genera: Archinamaqua Schawaller, 2012 and Menederopsis Koch, 1954 (Coleoptera: Tenebrionidae) from Namaqualand, South Africa - Kamiński, Marcin J.; Schawaller, Wolfgang (Zootaxa, 2019)
Based on the newly established synonymy of the type species (i.e., Menederopsis constrictus Koch, 1954 = Archinamaqua lyleae Schawaller, 2012 syn. nov.) the genus-group name Archinamaqua Schawaller, 2012 (Pimeliinae: Tentyriini) is interpreted as a junior synonym of Menederopsis Koch, 1954 (Tenebrioninae: Eurynotina). This newly interpreted taxon has a restricted distributional area on sand dunes in Namaqualand, western South Africa.